From chaos to coordination: leveraging technology for efficient bed management in a large and complex healthcare system - Wankar, Abhinav; Chaitanya, Krishna; Uddin, Mohammed A.; Jalota, Capri; Saxena, Kinjal; Mojasia, Gaurav; Pareek, Satish (International Journal of Research in Medical Sciences, 2025)
Background: Effective bed management is fundamental to hospital operations, significantly impacting patient care, resource utilization, and overall efficiency. AIG Hospitals, Hyderabad (India) accommodates 620 in-patient beds catering to more than 2,500 outpatients daily. The emergency department caters to over 70 visits each day and a 65% in-patient admission conversion rate. On average, the hospital handles 100 admissions and 100 internal transfer requests daily, maintaining a bed occupancy rate exceeding 75%. The Hospital tried handling through shared Excel sheets however bed management efficiency was a concern. Methods: To solve the problem, the hospital decided to leverage modern technology with good user interface to undertake real-time bed management. Results: This led to improvement in bed occupancy from 75% to 80%, increase in bed turnover rate by 11%, reduction in admission to arrival turnaround time (TAT) by 65% and improvement in net promoter score (NPS) by 14%. Average monthly admission went up by 12% on an average – converting to 323 additional admissions per month. The correlation for bed occupancy rate admission to arrival TAT and NPS was statistically significant. Conclusions: This article explores this innovative solution that revolutionized bed management by leveraging real-time tracking, intelligent analytics, and improved communication. As healthcare demand grows, hospitals must adopt innovative solutions. This study demonstrates how integrating a web-based bed management system can transform hospital operations, optimize resource use, and improve care delivery-setting a new benchmark in hospital efficiency.